“Evaluación del comportamiento agronómico del maní (Arachis hypogaea L.), a la aplicación de fijadores biológicos de nitrógeno en la zona de Babahoyo”. - Pincay Monserrate, Alexis Oswaldo (2019)
VIII. SUMMARY The peanut (Arachis hypogaea L.), is an oilseed that provides oil of excellent quality worldwide. In Ecuador approximately 12,000 to 15,000 ha of peanuts are cultivated, there being 1 6,000 ha on the coast with a production of 1 500 t. year 1. One of the negative factors in the production of peanuts is the lack of knowledge in the incorporation of beneficial microorganisms to the soil, which can improve soil fertility and help the development and yield of the crop, among the beneficial microorganisms are the nitrogen-fixing bacteria such as azotobacter and azospirillum that promote the development of plants. The objective of the experimental work is to evaluate the agronomic performance and yield of peanuts experimental (Arachis hypogaea L.), "INIAP - 381 ROSITA" to the application of Azotobacter, Azospirillum and levels of edaphic fertilization in the Babahoyo area. The present work was carried out in the farms of the Farm "San Pablo" of the Technical University of Babahoyo, located in the Km. 7½ of the Babahoyo - Montalvo road, The zone presented a humid tropical climate, with average temperature of 24.61 ° C; annual precipitation of 1 500.5 mm; relative humidity of 77% and 309 hours of annual average heliophany. The soil has a flat topography, loamy clay texture. The sowing was carried out in plots that presented areas of 4.29 m2 for which INIAP - Rosita 381 peanut variety was used. The treatments were distributed in a completely randomized block design using biological factors such as azotobacter, azospirillum and nitrogen fertilization. For the results of the data, the Tukey test at 95% significance was used. At 40, 60 and 120, plant height was evaluated, root length days to flowering. At the end of the crop cycle, number of capsules per plant, number of seeds per capsules, fresh and dry mass of plants, weight of 100 seeds, economic analysis was evaluated and a microorganism analysis was carried out to determine the number of bacteria population. Key Words: Peanuts, Factors, Azotobacter, Azospirillum Nitrogen and Treatments.